Translator and interpreter training and foreign language pedagogy - Krawutschke, Peter W. (John Benjamins Pub. Co, 1989)
Translator and Interpreter Training and Foreign Language Pedagogy; Editorial page; Title page; Copyright page; Table of contents; Introduction; Politics of Interpreter Education in Academia; Must Translator Training Remain Elitist?; Pendulum Swings in Language Teaching and Translation; Some Polemic Aspects of Translation in Foreign Language Pedagogy Revisited; Language Learning Before Translator/Interpreter Training; Teaching Conference Interpreting; Topical Issues in Translator Training at Universities; Standards and Evaluation in Translator Training
Print version record
Keywords: Electronic books